2018
DOI: 10.1101/390617
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Divergent methyl-coenzyme M reductase genes in a deep-subseafloor Archaeoglobi

Abstract: The methyl-coenzyme M reductase (MCR) complex is a key enzyme in archaeal methane generation and has recently been proposed to also be involved in the oxidation of short-chain hydrocarbons including methane, butane and potentially propane. The number of archaeal clades encoding the MCR complex continues to grow, suggesting that this complex was inherited from an ancient ancestor, or has undergone extensive horizontal gene transfer. Expanding the representation of MCR-encoding lineages through metagenomic appro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…In addition, the functional properties of the zm‐15 genome were examined with the KEGG database online (Kanehisa et al ., ). The heme motifs were predicted based on the conserved amino acid sequence of CxxCH (Boyd et al ., ) and the transmembrane domains were predicted using the TMHMM Server v. 2.0 (Moller et al ., ). The genome of the strain zm‐15 has been deposited in the NCBI databases under accession number of CP042908.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the functional properties of the zm‐15 genome were examined with the KEGG database online (Kanehisa et al ., ). The heme motifs were predicted based on the conserved amino acid sequence of CxxCH (Boyd et al ., ) and the transmembrane domains were predicted using the TMHMM Server v. 2.0 (Moller et al ., ). The genome of the strain zm‐15 has been deposited in the NCBI databases under accession number of CP042908.…”
Section: Methodsmentioning
confidence: 99%
“…A beta-oxidation pathway showing similarity, based on the presence of genes similar to atoB, paaH, crt, and bcd/etf , to those described in the methanogenic Archaeoglobus was also observed in Ca. Lunaplasma lacustris (Boyd et al , 2019), so it is possible that these organisms degrade fatty acids for energy conservation (Figure 2; Supplemental Table 8). ORFs annotated as acetate-CoA ligase ( acd) were also present, possibly conferring the ability to produce ATP through fermentation (Schäfer et al , 1993) and providing another route for energy conservation in this apparently versatile population.…”
Section: Resultsmentioning
confidence: 99%
“…In RBG-13-57-23, nrfD was also located next to a formate dehydrogenase subunit ( fdhD ), and in RBG-19FT-COMBO-69-17, one nrfD was between a molybdopterin oxidoreductase encoding gene annotated as encoding tetrothionate reductase subunit A ( ttrA) and dmsB . Boyd et al (2019) found dmsB and nrfD located on the same operon in an Archaeoglobus MAG recovered from the deep subseafloor and posited that these genes encode proteins used in sulfur redox chemistry (Boyd et al , 2019). Similarly, sulfate-reducing organisms use NrfD-like proteins as electron shuttles during sulfate reduction (Pereira et al , 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bathyarchaeota and Ca. Syntrophoarchaeum 42 . Consistent with this, Co_bin109 encodes a Wood-Ljungdahl pathway (including carbon monoxide dehydrogenase / acetyl-CoA synthase complex) for complete fatty acid oxidation (Supplementary Table 6) .…”
Section: Resultsmentioning
confidence: 99%